Ni / TiO x -NH2-MIL-101 nanocatalyst and its preparation method and application

By highly dispersing Ni nanoparticles on TiO2-NH2-MIL-101 nanoparticles, Ni/TiOx-NH2-MIL-101 nanocatalyst is formed, and the problems of low activity and easy agglomeration of non-precious metal catalysts are solved, and the high selectivity and stability of full decomposition and dehydrogenation of hydrazine hydrate are achieved.

CN119327516BActive Publication Date: 2025-03-21JIANGXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411855688.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing non-precious metal catalysts have low catalytic activity and are prone to agglomeration in hydrogen decomposition of hydrazine hydrate, making it difficult to achieve high selectivity and stability.

Method used

By highly dispersing Ni nanoparticles on TiO2-NH2-MIL-101 nanoparticles, Ni/TiOx-NH2-MIL-101 nanocatalyst is formed, and the strong metal-support interaction and the electron regulation of TiO2 are used to improve catalytic activity.

Benefits of technology

The 100% selectivity and high conversion frequency of catalytic decomposition and dehydrogenation of hydrazine hydrate were achieved (TOF value up to 443 h-1), and the stability and efficiency of the catalyst were maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327516B_ABST
    Figure CN119327516B_ABST
Patent Text Reader

Abstract

The present invention discloses Ni / TiO x ‑NH2‑MIL‑101 nanocatalyst and its preparation method and application, relating to the field of catalyst technology. The catalyst includes TiO x ‑NH2‑MIL‑101 nanoparticles and Ni nanoparticles dispersed thereon; wherein TiO x TiO2 and / or TiO 1.5 ;The content of Ni nanoparticles is 7.7 wt%-19.6 wt%;The preparation method includes: dispersing TiO2-NH2-MIL-101 powder in water, adding a nickel source precursor to disperse, and obtaining a suspension; adding a reducing agent to the suspension for reduction reaction until no bubbles are generated, and obtaining; The present invention also provides the application of the catalyst in catalyzing the decomposition of hydrazine hydrate to produce hydrogen. The beneficial effect of the present invention is that due to the strong interaction between the metal-carrier, the introduction of ultrafine Ni metal nanoparticles and the modifier TiO2, it has an electronic regulation effect on Ni, so that the catalyst of the present invention has high catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts and specifically relates to a Ni / TiO x -NH2-MIL-101 nanocatalyst and its preparation method and application. Background Art

[0002] As a green and sustainable energy carrier, hydrogen (H2) has attracted much attention due to its huge energy density and environmental friendliness. However, the safe and efficient storage of hydrogen remains a key challenge. Nowadays, chemical hydrogen storage has been recognized as an efficient and convenient method. Hydrazine hydrate (N2H4・H2O) has become a highly regarded chemical hydrogen storage material due to its high capacity (8.0 wt%) and safe storage and transportation. Under suitable catalysts and reaction conditions, N2H4 can be completely decomposed into H2 and N2, as shown in reaction equation (1). However, if the catalyst or reaction conditions are not suitable, the decomposition of N2H4 can also be through an incomplete decomposition route, as shown in reaction equation (2), that is, it is decomposed into NH3 and N2, which reduces the hydrogen production efficiency, and the generated NH3 will poison the catalyst. Therefore, the development of highly selective and highly stable catalytic materials is of great significance to achieve complete hydrogen production from N2H4.

[0003] N2H4→ N2(g) + 2H2(g) (1)

[0004] 3N2H4→ 4NH3(g) + N2(g)(2)

[0005] Currently, most of the efficient catalysts for hydrazine hydrate decomposition to produce hydrogen contain precious metals. Non-precious metal catalysts, especially nickel catalysts, have been shown to have good activity and selectivity in hydrazine hydrate hydrolysis, but their catalytic activity is still unsatisfactory compared with precious metal-based catalysts, and they are prone to agglomeration. Therefore, there is an urgent need to develop cost-effective non-precious metal catalysts for the rapid catalytic decomposition of hydrazine hydrate to produce hydrogen. Summary of the invention

[0006] The purpose of the present invention is to at least solve the problems of low catalytic activity and easy agglomeration of non-precious metal catalysts in the prior art, and to provide a Ni / TiO x -NH2-MIL-101 nanocatalyst and its preparation method and application.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect of the present invention, there is provided a Ni / TiO x -NH2-MIL-101 nanocatalyst,

[0009] Including TiO x-NH2-MIL-101 nanoparticles and dispersed in the TiO x -Ni nanoparticles on NH2-MIL-101 nanoparticles;

[0010] Wherein, the TiO x TiO in NH2-MIL-101 nanoparticles x TiO2 and / or TiO 1.5 ;

[0011] The Ni / TiO x -Calculated based on the total mass of the NH2-MIL-101 nanocatalyst, the content of the Ni nanoparticles is 7.7 wt%-19.6 wt%.

[0012] The Ni / TiO x -NH2-MIL-101 nanocatalyst has excellent activity due to the strong metal-support interaction, ultrafine Ni metal nanoparticles and the introduction of the modifier TiO2, which enables it to electronically regulate Ni. The catalyst has the characteristics of small particle size, multiple catalytic active sites, and high catalytic activity and stability. It is a catalyst with great development prospects.

[0013] Optionally, the Ni / TiO x -Calculation of the total mass of NH2-MIL-101 nanocatalyst, the Ni / TiO x The Ti content in -NH2-MIL-101 nanocatalyst is 1.7 wt%-6.8 wt%.

[0014] Optionally, the average particle size of the Ni nanoparticles is 3.0 nm-3.4 nm.

[0015] Optionally, the Ni / TiO x -NH2-MIL-101 nanocatalyst has a specific surface area of ​​100m 2 g -1 -140 m 2 g -1 ;

[0016] The Ni / TiO x -NH2-MIL-101 nanocatalyst has a total pore volume of 3.2 nm-3.9 nm;

[0017] The TiO x - The particle size of NH2-MIL-101 nanoparticles is 300 nm-500 nm;

[0018] The Ni / TiO xThe average particle size of -NH2-MIL-101 nanocatalyst is 300 nm-500 nm.

[0019] The second aspect of the present invention provides a Ni / TiO x -NH2-MIL-101 nanocatalyst preparation method, which comprises the following steps:

[0020] Dispersing TiO2-NH2-MIL-101 powder in water, adding nickel source precursor and continuing to disperse to obtain a suspension;

[0021] A reducing agent is added to the suspension to carry out a reduction reaction until no bubbles are generated to obtain Ni / TiO x -NH2-MIL-101 nanocatalyst.

[0022] The present invention prepares NH2-MIL-101 modified by TiO2 by a simple and environmentally friendly wet chemical method and uses it as a carrier. The carrier TiO2-NH2-MIL-101 introduces TiO2 as a modifier, which is a reducible metal oxide that can promote electron transfer between the carrier and active metal nanoparticles, thereby adjusting the electronic state of the metal active site and improving the catalytic performance.

[0023] Optionally, the mass ratio of the TiO2-NH2-MIL-101 powder to the nickel source precursor is 0.03 g-0.09 g: 23.7 mg-59.4 mg;

[0024] The nickel source precursor includes at least one of nickel chloride, nickel nitrate or nickel sulfate;

[0025] The reducing agent includes sodium borohydride.

[0026] Optionally, the preparation method of the TiO2-NH2-MIL-101 powder comprises the following steps:

[0027] The NH2-MIL-101 powder is uniformly dispersed in anhydrous methanol, tetrabutyl titanate is added and mixed uniformly, and then refluxed at 80°C-90°C for 8 h-12 h; the product is washed and dried to obtain TiO2-NH2-MIL-101 powder;

[0028] The ratio of the added amount of NH2-MIL-101 to tetrabutyl titanate is 0.3 g-0.5 g: 0.03 mL-0.12 mL.

[0029] Optionally, the method for preparing the NH2-MIL-101 powder comprises the following steps:

[0030] Slowly adding chromium nitrate and 2-aminoterephthalic acid to the aqueous solution containing NaOH, stirring at room temperature for 20 minutes to 40 minutes to obtain a mixture;

[0031] The mixture is transferred to a high pressure reaction vessel and maintained at 140° C. to 160° C. for 10 to 14 hours, cooled and centrifuged to collect the product;

[0032] The product is washed and dried to obtain NH2-MIL-101 powder;

[0033] Wherein, the usage ratio of the chromium nitrate and the 2-aminoterephthalic acid is 3 g-3.4 g: 1 g-1.8 g.

[0034] The third aspect of the present invention provides the Ni / TiO x -NH2-MIL-101 nanocatalyst or Ni / TiO obtained by the above preparation method x -Application of NH2-MIL-101 nanocatalyst in catalytic decomposition of hydrazine hydrate to produce hydrogen.

[0035] Optionally, the Ni / TiO x The temperature of catalytic decomposition of hydrazine hydrate to produce hydrogen by -NH2-MIL-101 nanocatalyst is 323-353 K.

[0036] The Ni / TiO x -NH2-MIL-101 nanocatalysts catalyzed hydrazine hydrate to produce hydrogen and showed 100% H2 selectivity. The catalytic reaction rate was significantly improved with the increase of temperature. At 343 K, the prepared Ni / TiO x The catalytic decomposition and dehydrogenation of hydrazine hydrate by -NH2-MIL-101 nanocatalyst only takes 2.8 min, and its turnover frequency (TOF) value is as high as 443 h -1 .

[0037] The present invention has at least one of the following beneficial effects:

[0038] (1) In the present invention, NH2-MIL-101 modified with TiO2 is prepared by a simple and environmentally friendly wet chemical method, and is used as a carrier to highly disperse ultrafine Ni nanoparticles with an average particle size of about 3.0-3.4 nm in TiO2 by a simple, green and low-cost wet chemical method. x -NH2-MIL-101 nanoparticles, TiO x -NH2-MIL-101 supported Ni nanocatalyst (Ni / TiO x-NH2-MIL-101). This method introduces TiO2 as a modifier to promote the electron transfer between the carrier and the active metal nanoparticles, thereby adjusting the electronic state of the metal active sites and improving the catalytic performance. XRD, FTIR, TEM and XPS characterization analysis show that during the reduction process of the carrier TiO2-NH2-MIL-101 nanosheets, part of the Ti 4+ The species is reduced to Ti on the catalyst 3+ , which is beneficial to optimize the electronic structure of active metal Ni nanoparticles, making their surface electron-rich, thereby significantly improving the catalyst activity.

[0039] (2) Ni / TiO prepared by the present invention x The excellent activity of -NH2-MIL-101 nanocatalyst is attributed to the electron-rich, good dispersion and small size of Ni NPs (nickel nanoparticles), as well as the x -Strong EMSI (electronic metal-support interaction) between NH2 and MIL-101.

[0040] (3) Ni / TiO prepared by the present invention x -NH2-MIL-101 catalyst exhibits excellent catalytic performance, 100% H2 selectivity and remarkable durability. x The TOF value of -NH2-MIL-101 for catalytic decomposition of hydrazine hydrate to produce hydrogen at 343 K is 443 h -1 .

[0041] (4) The catalyst provided by the present invention has the advantages of high efficiency, stability and low cost of preparation, and the catalyst accelerates the practical application of hydrazine hydrate as an efficient hydrogen donor in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The Ni / TiO prepared in Example 1 of the present invention is shown. x - X-ray diffraction patterns of NH2-MIL-101 nanocatalyst and Ni / NH2-MIL-101, TiO2-NH2-MIL-101 and NH2-MIL-101 prepared in Comparative Examples 1 to 3;

[0043] Figure 2 The Ni / TiO prepared in Example 1 of the present invention is shown. x - Fourier transform infrared spectra of Ni / NH2-MIL-101, TiO2-NH2-MIL-101 and NH2-MIL-101 prepared from NH2-MIL-101 nanocatalyst and Comparative Examples 1 to 3;

[0044] Figure 3The Ni / TiO prepared in Example 1 of the present invention is shown x - Nitrogen adsorption and desorption curves of Ni / NH2-MIL-101, TiO2-NH2-MIL-101 and NH2-MIL-101 prepared from NH2-MIL-101 nanocatalyst and Comparative Examples 1 to 3;

[0045] Figure 4 The Ni / TiO prepared in Example 1 of the present invention is shown. x - pore size distribution diagram of Ni / NH2-MIL-101, TiO2-NH2-MIL-101 and NH2-MIL-101 prepared from NH2-MIL-101 nanocatalyst and Comparative Examples 1 to 3;

[0046] Figure 5 The Ni / TiO prepared in Example 1 of the present invention is shown. x -X-ray photoelectron spectra of the NH2-MIL-101 nanocatalyst and the Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1;

[0047] Figure 6 The Ni / TiO prepared in Example 1 of the present invention is shown. x - Field emission scanning electron microscopy (a) and transmission electron microscopy (b and c) images of NH2-MIL-101 nanocatalyst and particle size statistics of Ni nanoparticles (d);

[0048] Figure 7 Shown are the transmission electron microscope images (shown in a) of the Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1 of the present invention and the particle size statistics of Ni nanoparticles (shown in b);

[0049] Figure 8 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst and Ni / NH2-MIL-101, TiO2-NH2-MIL-101 and Ni nanocatalyst prepared in Comparative Examples 1, 2 and 4, respectively, under 343 K, catalyzing the decomposition of hydrazine hydrate to produce hydrogen;

[0050] Fig. 9 The Ni / TiO prepared in Example 1, Comparative Example 7 and Comparative Example 8 are shown. x -NH2-MIL-101, Ni / TiO x -UiO-66 and Ni / TiO x-MIL-96 (Al) nanocatalyst and the performance diagram of Ni / NH2-MIL-101, Ni / UiO-66 and Ni / MIL-96 (Al) nanocatalysts prepared in Comparative Examples 1, 5 and 6, respectively, catalyzing the decomposition of hydrazine hydrate to produce hydrogen at 343 K;

[0051] Fig.10 The Ni / TiO prepared in Examples 1 to 4 of the present invention is shown. x -NH2-MIL-101 nanocatalyst catalyzes the decomposition of hydrazine hydrate at 343 K to produce hydrogen;

[0052] Fig.11 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst catalyzes the decomposition of hydrazine hydrate to produce hydrogen at different temperatures;

[0053] Fig.12 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst catalyzes the decomposition of hydrazine hydrate to produce hydrogen at 343 K for cyclic use. DETAILED DESCRIPTION

[0054] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0055] Example 1

[0056] A Ni / TiO x -NH2-MIL-101 nanocatalyst preparation method, which specifically comprises the following steps:

[0057] (1) Preparation of TiO2-NH2-MIL-101

[0058] First, 0.40 g of NH2-MIL-101 was dispersed into 30 mL of methanol in a flask under ultrasound, and then 0.09 mL of tetrabutyl titanate was added to the mixture, and then the solution was refluxed at 85 °C for 10 h. Then, the precipitate was washed 3 times with excess ethanol and dried in vacuum at 40 °C overnight to obtain TiO2-NH2-MIL-101.

[0059] Wherein, NH2-MIL-101 powder is obtained by the following steps:

[0060] 3.2 g of chromium nitrate and 1.44 g of 2-aminoterephthalic acid were slowly added to 60 mL of H2O solution containing 0.8 g of NaOH. The mixture, which was stirred at room temperature for 30 min, was then transferred to a 100 mL Teflon-lined stainless steel autoclave and kept at 150 °C for 12 h. After natural cooling, the resulting mixture was collected by centrifugation at 7000 rpm for 2 min. The obtained green powder was washed several times with water, DMF and methanol, respectively, and dried at 10 °C overnight. Then, activated NH2-MIL-101 was obtained.

[0061] (2) Ni / TiO x Preparation of -NH2-MIL-101 nanocatalyst

[0062] 70 mg of TiO2-NH2-MIL-101 white powder prepared in step (1) was dispersed in 5 mL of deionized water, 48.4 mg of nickel chloride was added, and ultrasonic treatment was performed at room temperature for 30 min. 50 mg of sodium borohydride was added for reduction until no bubbles were generated, and Ni / TiO2 with Ni and Ti contents of 14.3 wt% and 1.7 wt%, respectively, was obtained. x -NH2-MIL-101 nanocatalyst.

[0063] Comparative Example 1

[0064] A method for preparing a Ni / NH2-MIL-101 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the amount of tetrabutyl titanate in step (1) of Example 1 is changed from 0.09 mL to 0, and the other steps are exactly the same, thereby obtaining a Ni / NH2-MIL-101 nanocatalyst with a Ni content of 14.3 wt%.

[0065] Comparative Example 2

[0066] A method for preparing a TiO2-NH2-MIL-101 nanomaterial, the preparation method of which is similar to the method in Example 1, except that the amounts of nickel chloride and sodium borohydride in step (2) of Example 1 are both changed to 0 mg, and the other steps are exactly the same, to obtain a TiO2-NH2-MIL-101 nanocatalyst with Ni and Ti contents of 0 wt% and 1.7 wt%, respectively.

[0067] Comparative Example 3

[0068] A method for preparing NH2-MIL-101 nanomaterials, 3.2 g of chromium nitrate and 1.44 g of 2-aminoterephthalic acid are slowly added to 60 mL of H2O solution containing 0.8 g of NaOH. The mixture stirred at room temperature for 30 minutes is then transferred to a 100 mL Teflon-lined stainless steel autoclave and kept at 150 °C for 12 hours. After natural cooling, the resulting mixture is collected by centrifugation at 7000 rpm for 2 min. The obtained green powder is washed several times with water, DMF and methanol, respectively, and dried at 10 °C overnight. Then, activated NH2-MIL-101 is obtained.

[0069] Comparative Example 4

[0070] A method for preparing a Ni nanocatalyst, wherein the preparation method is similar to the method of step (2) in Example 1, the only difference being that TiO2-NH2-MIL-101 white powder is not added in step (2), and the other steps are exactly the same as step (2) in Example 1 to obtain a Ni nanocatalyst.

[0071] Comparative Example 5

[0072] A method for preparing a Ni / UiO-66 nanocatalyst, wherein the preparation method is similar to the method in Example 1, the only difference being that TiO2-NH2-MIL-101 in step (2) of Example 1 is replaced by UiO-66, and the other steps are exactly the same, thereby obtaining a Ni / UiO-66 nanocatalyst having a Ni content of 14.3 wt%.

[0073] Comparative Example 6

[0074] A method for preparing a Ni / MIL-96(Al) nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that TiO2-NH2-MIL-101 in step (2) of Example 1 is replaced by MIL-96(Al), and the other steps are exactly the same, thereby obtaining a Ni / MIL-96(Al) nanocatalyst having a Ni content of 14.3 wt%.

[0075] Comparative Example 7

[0076] A Ni / TiO x The preparation method of the UiO-66 nanocatalyst is similar to that in Example 1, except that the NH2-MIL-101 in step (1) of Example 1 is replaced with UiO-66. The other steps are exactly the same, and a Ni / TiO nanocatalyst having Ni and Ti contents of 14.3 wt% and 1.7 wt% is obtained. x -UiO-66 nanocatalyst.

[0077] Comparative Example 8

[0078] A Ni / TiO x -MIL-96 (Al) nanocatalyst preparation method, the preparation method is similar to the method in Example 1, the only difference is that the NH2-MIL-101 in step (1) of Example 1 is replaced by MIL-96 (Al), the other steps are exactly the same, and the Ni and Ti contents are 14.3 wt% and 1.7 wt% respectively. x -MIL-96(Al) nanocatalyst.

[0079] Example 2

[0080] A Ni / TiO x The preparation method of -NH2-MIL-101 nanocatalyst is similar to the method in Example 1, the only difference is that the amount of nickel chloride in step (2) of Example 1 is changed from 48.4 mg to 23.8 mg, and the other steps are exactly the same.

[0081] Example 3

[0082] A Ni / TiO x The preparation method of -NH2-MIL-101 nanocatalyst is similar to the method in Example 1, the only difference is that the amount of nickel chloride in step (2) of Example 1 is changed from 48.4 mg to 35.7 mg, and the other steps are exactly the same.

[0083] Example 4

[0084] A Ni / TiO x The preparation method of -NH2-MIL-101 nanocatalyst is similar to the method in Example 1, the only difference is that the amount of nickel chloride in step (2) of Example 1 is changed from 48.4 mg to 59.4 mg, and the other steps are exactly the same.

[0085] The relevant characterization data of some materials prepared in the above embodiments and comparative examples are as follows:

[0086] Figure 1 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst, the Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1, the TiO2-NH2-MIL-101 nanocatalyst prepared in Comparative Example 2, and the NH2-MIL-101 nanocatalyst prepared in Comparative Example 3; and by Figure 1It can be seen that the XRD pattern of Comparative Example 2 is the same as that of Comparative Example 3, which means that their structures are well maintained after TiO2 modification. However, Comparative Example 1 and Example 1 show broad low-crystalline diffraction peaks after NaBH4 reduction, which may be due to the highly dispersed Ni NPs (nickel nanoparticles) uniformly covering the MOF surface and pores. It should be noted that Comparative Example 1 and Example 1 do not show any characteristic diffraction peaks related to Ni and / or TiO2 species, which may be due to the excellent dispersibility of Ni on NH2-MIL-101 and may be due to the limitations of XRD technology in detecting smaller NPs.

[0087] Figure 2 The Ni / TiO prepared in Example 1 of the present invention is shown. x Fourier transform infrared spectra of the NH2-MIL-101 nanocatalyst, the Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1, the TiO2-NH2-MIL-101 nanocatalyst prepared in Comparative Example 2, and the NH2-MIL-101 nanocatalyst prepared in Comparative Example 3; Comparative Example 3 at 1654 cm -1 The IR peak at 1340 cm −1 There is a tiny peak at 3475 cm -1 and 3399 cm -1 The double peaks at can be assigned to the asymmetric and symmetric vibrations of the amino group. It is worth noting that the characteristic peak positions of Comparative Example 1 and Example 1 are slightly red-shifted compared with Comparative Example 2. This indicates that the chemical environment around Comparative Example 2 has changed, which may be due to the strong electronic effect interaction between Ni NPs and TiO2-NH2-MIL-101.

[0088] Figure 3 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst, Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1, TiO2-NH2-MIL-101 nanocatalyst prepared in Comparative Example 2, and NH2-MIL-101 nanocatalyst prepared in Comparative Example 3. According to the IUPAC classification, all four samples showed the same type I isotherm, indicating that micropores mainly existed in the samples. However, a tiny hysteresis loop was also observed, which was related to a small amount of capillary condensation. The similar behavior of the samples shows that the pore structure of Comparative Example 2 is well retained after TiO2 modification. The BET surface areas of Comparative Example 3, Comparative Example 2, Comparative Example 1, and Example 1 are 1657 m 2 g-1 、1415m 2 g -1 、557m 2 g -1 and 124 m 2 g -1 , decreasing in the order of Comparative Example 3 > Comparative Example 2 > Comparative Example 1 > Example 1. The same trend was observed in the total pore volume.

[0089] Figure 4 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst, Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1, TiO2-NH2-MIL-101 nanocatalyst prepared in Comparative Example 2, and NH2-MIL-101 nanocatalyst prepared in Comparative Example 3. The reduction in surface area and pore volume of Comparative Example 2 may be due to the partial occupation of the pores in NH2-MIL-101 by the TiO2 introduced into the pores. The reduction in specific surface area of ​​Example 1 relative to Comparative Example 2 may be due to the fact that the Ni loading occupies a certain area, which once again proves the successful loading of metal nanoparticles.

[0090] Figure 5 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst and the Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1; and by Figure 5 It can be seen that the full spectrum of Example 1 proves the presence of Ni, Cr, Ti, O, N and C elements. For the Ni 2p3 / 2 spectrum of Example 1, the binding energy of about 850.4 eV is attributed to metallic Ni(0), and the binding energy of 853.5 eV belongs to Ni 2+ , the binding energy at 858.9 eV is attributed to its satellite peak. The presence of oxidized Ni may be due to partial oxidation of the catalyst during sample preparation. For the Cr 2p of Example 1, the binding energies at 585.2 and 575.6 eV are attributed to Cr2O3. For the Ti 2p of Example 1, the binding energies at 458.2 and 463.0 eV correspond to Ti 4+ 2p 3 / 2 and Ti 4+ 2p 1 / 2 ; Meanwhile, the binding energies of 456.1 and 461.6 eV are assigned to Ti 3+ 2p 3 / 2 and Ti 3+ 2p 1 / 2 .Ti 3+ The existence of species is due to Ti4+ A portion of the Ni 2p in Example 1 (850.4 eV) is reduced during the catalyst reduction process. For the N 1s of Example 1, the binding energy at 400.8 eV is attributed to the amino group. In addition, the Ni 2p in Example 1 (850.4 eV) is significantly higher than that in Comparative Example 1 (850.9 eV). 3 / 2 shifted to a lower binding energy, indicating that some electrons were removed from TiO x In addition, compared with Comparative Example 1 (575.3 eV), Cr in Example 1 (575.3 eV) 3+ 2p 3 / 2 The binding energy value of NH-MIL-101 is higher, which indicates that some electrons are transferred from NH-MIL-101 to TiO x The above XPS analysis results show that the TiO x Doping into NH2-MIL-101 can increase the electron density on the surface of active metal Ni, which is beneficial to promote the breaking of NH bonds and thus improve the catalytic efficiency.

[0091] Figure 6 The Ni / TiO prepared in Example 1 of the present invention is shown. x -NH2-MIL-101 nanocatalyst scanning electron microscope image (shown in a), transmission electron microscope image (shown in b), high-resolution transmission electron microscope image (shown in c) and particle size statistics of Ni nanoparticles (shown in d); and by Figure 6 It can be seen that Ni nanoparticles with an average size of 3.2 nm are uniformly dispersed in the TiO x -NH2-MIL-101.

[0092] Figure 7 Shown are the transmission electron microscope images (shown in a) of the Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1 of the present invention and the particle size statistics of the Ni nanoparticles (shown in b); and Figure 7 It can be seen that without the introduction of TiO x The Ni nanoparticles loaded on the modified NH2-MIL-101 were larger in size (4.4 nm).

[0093] Example 5

[0094] The Ni / TiO prepared in Example 1 of the present invention x -NH2-MIL-101 nanocatalyst, Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1, TiO2-NH2-MIL-101 nanocatalyst prepared in Comparative Example 2 and Ni nanocatalyst prepared in Comparative Example 4 catalyze hydrazine hydrate decomposition to produce hydrogen, and the specific process is as follows:

[0095] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 15 mmol of NaOH was added. The amount of the catalyst was the amount of the catalyst prepared in each example. 100 μL (2 mmol) of hydrazine hydrate was added at 343 K and normal pressure to react. The hydrogen production performance is shown in the figure. Figure 8 As shown, the preparation conditions of the nanocatalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 and the results of the catalytic reactions are shown in Table 1.

[0096] Table 1 Performance of hydrazine hydrate hydrogen production by nanocatalyzed catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4

[0097]

[0098] As shown in Table 1, the unsupported Ni nanocatalyst prepared in Comparative Example 4 exhibited low H2 selectivity and activity for the dehydrogenation reaction. After the Ni NPs were grown on NH2-MIL-101 (i.e., Comparative Example 1), the H2 selectivity and catalytic activity were greatly enhanced. When TiO2-modified NH2-MIL-101 was used as a support, the obtained Example 1 exhibited the best catalytic performance (443 h -1 ), respectively compared with Example 4 (15 h -1 ) and Comparative Example 1 (57 h -1 ) are about 29.5 and 7.8 times higher.

[0099] Example 6

[0100] The Ni / TiO prepared in Example 1, Comparative Example 7 and Comparative Example 8 of the present invention are used. x -NH2-MIL-101, Ni / TiO x -UiO-66 and Ni / TiO x -MIL-96 (Al) nanocatalyst and the Ni / NH2-MIL-101, Ni / UiO-66 and Ni / MIL-96 (Al) nanocatalysts prepared in Comparative Examples 1, 5 and 6 catalyze the decomposition of hydrazine hydrate to produce hydrogen. The specific process is as follows:

[0101] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 15 mmol of NaOH was added. The amount of the catalyst was the amount of the catalyst prepared in each embodiment and comparative example. 100 uL (2 mmol) of hydrazine hydrate was added at 343 K and normal pressure to react. The hydrogen production performance diagram is shown in FIG. Fig. 9 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 2.

[0102] Table 2 Performance of each nanocatalyst prepared in Example 1 and Comparative Example 1, Comparative Example 5-Comparative Example 8 for catalytic hydrazine hydrate hydrogen production

[0103]

[0104] It can be seen from Table 2 that the Ni / TiO prepared in Example 1 x -NH2-MIL-101 nanocatalyst over TiO x The activity of the modified catalyst in catalyzing hydrogen production from hydrazine hydrate is higher than that of the unmodified Ni / NH2-MIL-101 nanocatalyst prepared in Comparative Example 1; although the hydrogen selectivity of Ni / NH2-MIL-101 prepared in Comparative Example 1 can reach 83%, its catalytic activity is much lower than that of Ni / TiO x -NH2-MIL-101. This is because the MOF carrier is TiO x After modification, not only can the size of active metal NPs be reduced and their dispersibility be improved, but also the electron density of active metal NPs can be optimized, thereby significantly enhancing the catalytic performance. The performance of comparative examples 7 and 8 in catalyzing hydrazine hydrate to produce hydrogen was further tested, and the H2 selectivity and conversion frequency of comparative examples 5 and 6 were compared. It can be concluded that the MOF carrier, which originally had poor performance in catalyzing hydrazine hydrate to produce hydrogen, was modified by TiO x After modification, the hydrogen production performance has been greatly improved.

[0105] Example 7

[0106] The Ni / TiOx-NH2-MIL-101 nanocatalyst prepared in Example 1 of the present invention catalyzes the decomposition of hydrazine hydrate to produce hydrogen at different metal contents, and the specific process is as follows:

[0107] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 15 mmol of NaOH was added. The amount of the catalyst was the amount of the catalyst prepared in Example 1 to Example 4. 100 uL (2 mmol) of hydrazine hydrate was added at 343 K and normal pressure to react. The hydrogen production performance diagram is shown in the figure. Fig.10 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 3.

[0108] Table 3 Performance of hydrazine hydrate hydrogen production by nanocatalyzed catalysts prepared in Example 1, Example 2-Example 4

[0109]

[0110] It can be seen from Table 3 that the Ni / TiO prepared in Examples 1, 2-4 x-NH2-MIL-101 nanocatalyst catalyzes hydrazine hydrate to produce hydrogen and shows 100% H2 selectivity. With the increase of catalyst concentration, the reaction rate gradually increases. According to the relationship between ln k and ln[Ni], the slope is calculated to be 0.97, which is close to 1, indicating that Ni / TiO x The dehydrogenation reaction catalyzed by -NH2-MIL-101 is approximately a first-order reaction relative to the catalyst concentration.

[0111] Example 8

[0112] The Ni / TiO prepared in Example 1 of the present invention x -NH2-MIL-101 nanocatalyst catalyzes the decomposition of hydrazine hydrate to produce hydrogen at different temperatures. The specific process is as follows:

[0113] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 15 mmol of NaOH was added. 100 uL (2 mmol) of hydrazine hydrate was added at 323 K, 333 K, 343 K, and 353 K under normal pressure to react. The hydrogen production performance is shown in the figure. Fig.11 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 4.

[0114] Table 4 Ni / TiO prepared in Example 1 x -NH2-MIL-101 nanocatalyst catalytic hydrazine hydrate hydrogen production performance table at different catalytic temperatures

[0115]

[0116] It can be seen from Table 4 that Ni / TiO x -NH2-MIL-101 nanocatalysts catalyzed hydrazine hydrate to produce hydrogen and showed 100% H2 selectivity. The catalytic reaction rate was significantly improved with the increase of temperature. At 343 K, the prepared Ni / TiO x The catalytic decomposition and dehydrogenation of hydrazine hydrate by -NH2-MIL-101 nanocatalyst only takes 2.8 min, and its turnover frequency (TOF) value is as high as 443 h -1 This is mainly attributed to the fact that high temperature can activate the catalyst and thus effectively improve the catalytic reaction activity. According to the Arrhenius equation, Ni / TiO x The activation energy of the hydrogen production reaction of hydrazine hydrate catalyzed by -NH2-MIL-101 is 50.9 kJ / mol.

[0117] Example 9

[0118] The Ni / TiO prepared in Example 1 of the present invention x-NH2-MIL-101 nanocatalyst catalyzes the decomposition of hydrazine hydrate to produce hydrogen. The specific process is as follows:

[0119] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 15 mmol of NaOH was added. 100 uL of hydrazine hydrate was added at 343 K and atmospheric pressure for reaction. The reaction was repeated 20 times. The hydrogen production performance is shown in the figure below. Fig.12 shown.

[0120] from Fig.12 It can be seen that Ni / TiO x -NH2-MIL-101 nanocatalyst has good cyclic stability for the decomposition of hydrazine hydrate to produce hydrogen. After repeated use for 20 times, the amount of gas produced by hydrazine hydrate catalyzed by the catalyst did not decrease, and it can still maintain 63.2% of the initial catalytic activity, indicating that the catalyst has good catalytic activity and cyclic stability.

[0121] The Ni / TiO prepared by the present invention x The excellent activity of -NH2-MIL-101 nanocatalyst is attributed to the electron-rich, good dispersion and small size of Ni NPs (nickel nanoparticles), as well as the x -Strong EMSI (electronic metal-support interaction) between NH2 and MIL-101.

[0122] In summary, the method for preparing the catalyst of the present invention is simple to operate and low in cost. The obtained catalyst has the characteristics of small particle size, multiple catalytic active sites, etc., and has high catalytic activity and stability, and is a catalyst with great development prospects.

[0123] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A Ni / TiO x -NH2-MIL-101 nanocatalyst, characterized in that Including TiO x -NH2-MIL-101 nanoparticles and dispersed in the TiO x -Ni nanoparticles on NH2-MIL-101 nanoparticles; Wherein, the TiO x TiO in NH2-MIL-101 nanoparticles x For TiO2 and TiO 1.5 ; The Ni / TiO x - calculated based on the total mass of the NH2-MIL-101 nanocatalyst, the content of the Ni nanoparticles is 7.7wt%-19.6wt%; The average particle size of the Ni nanoparticles is 3.0 nm-3.4 nm; The preparation method of NH2-MIL-101 powder comprises the following steps: Slowly adding chromium nitrate and 2-aminoterephthalic acid to the aqueous solution containing NaOH, stirring at room temperature for 20 minutes to 40 minutes to obtain a mixture; The mixture is transferred to a high pressure reaction vessel and maintained at 140° C. to 160° C. for 10 to 14 hours, cooled and centrifuged to collect the product; The product was washed and dried to obtain NH2-MIL-101 powder.

2. Ni / TiO according to claim 1 x -NH2-MIL-101 nanocatalyst, characterized in that The Ni / TiO x -Calculation of the total mass of NH2-MIL-101 nanocatalyst, the Ni / TiO x The Ti content in -NH2-MIL-101 nanocatalyst is 1.7 wt%-6.8 wt%.

3. A Ni / TiO according to any one of claims 1 to 2 x -NH2-MIL-101 nanocatalyst preparation method, characterized in that, The following steps are involved: Dispersing TiO2-NH2-MIL-101 powder in water, adding nickel source precursor and continuing to disperse to obtain a suspension; A reducing agent is added to the suspension to carry out a reduction reaction until no bubbles are generated to obtain Ni / TiO x -NH2-MIL-101 nanocatalyst.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the TiO2-NH2-MIL-101 powder to the nickel source precursor is 0.03 g-0.09 g: 23.7 mg-59.4 mg; The nickel source precursor includes at least one of nickel chloride, nickel nitrate or nickel sulfate; The reducing agent includes sodium borohydride.

5. The preparation method according to claim 3, characterized in that: The preparation method of the TiO2-NH2-MIL-101 powder comprises the following steps: The NH2-MIL-101 powder is uniformly dispersed in anhydrous methanol, tetrabutyl titanate is added and mixed uniformly, and then refluxed at 80°C-90°C for 8 h-12 h; the product is washed and dried to obtain TiO2-NH2-MIL-101 powder; The ratio of the added amounts of NH2-MIL-101 to tetrabutyl titanate is 0.3 g-0.5 g: 0.03 mL-0.12 mL.

6. The preparation method according to claim 5, characterized in that: The preparation method of the NH2-MIL-101 powder comprises the following steps: Slowly adding chromium nitrate and 2-aminoterephthalic acid to the aqueous solution containing NaOH, stirring at room temperature for 20 minutes to 40 minutes to obtain a mixture; The mixture is transferred to a high pressure reaction vessel and maintained at 140° C. to 160° C. for 10 to 14 hours, cooled and centrifuged to collect the product; The product is washed and dried to obtain NH2-MIL-101 powder; Wherein, the usage ratio of the chromium nitrate and the 2-aminoterephthalic acid is 3 g-3.4 g: 1 g-1.8 g.

7. A Ni / TiO as claimed in any one of claims 1 to 2 x -Application of NH2-MIL-101 nanocatalyst in catalytic decomposition of hydrazine hydrate to produce hydrogen.

8. The use according to claim 7, characterized in that: The Ni / TiO x The temperature of catalytic decomposition of hydrazine hydrate to produce hydrogen by -NH2-MIL-101 nanocatalyst is 323-353 K.

Citation Information

Patent Citations

  • TiO2 / MIL-101 composite catalyst for photocatalytic water splitting and preparation method and applications thereof

    CN103240130A

  • Metal loading type catalyst, and preparation method and applications thereof

    CN107670694A